2013
DOI: 10.4187/respcare.02053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training on Inspiratory Load Compensation in Weaned and Unweaned Mechanically Ventilated ICU Patients

Abstract: BACKGROUND While inspiratory muscle weakness is common in prolonged mechanical ventilation, inspiratory muscle strength training (IMST) can facilitate strengthening and ventilator weaning. However, the inspiratory load compensation (ILC) responses to threshold loads are not well characterized in patients. We retrospectively compared ILC responses according to the clinical outcomes of IMST (ie, maximum inspiratory pressure [PImax], weaning outcome), in difficult-to-wean ICU patients. METHODS Sixteen tracheost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 29 publications
0
15
0
3
Order By: Relevance
“…26 Smith and co-workers 18 found that prolonged-weaning patients who continued to fail SBTs had blunted ILC responses, similar to those who failed weaning for the first time. 27 Blunted ILC response may be due to depressed neuromuscular output and/or neuroventilatory inefficiency.…”
Section: See the Original Study On Page 22mentioning
confidence: 96%
See 4 more Smart Citations
“…26 Smith and co-workers 18 found that prolonged-weaning patients who continued to fail SBTs had blunted ILC responses, similar to those who failed weaning for the first time. 27 Blunted ILC response may be due to depressed neuromuscular output and/or neuroventilatory inefficiency.…”
Section: See the Original Study On Page 22mentioning
confidence: 96%
“…After training the average PIF and V T increased significantly: PIF range 16 -18%, V T range 14 -42%. However, there was a large overlap between before and after IMST (see figure 6 in Smith et al 18 ).…”
Section: See the Original Study On Page 22mentioning
confidence: 97%
See 3 more Smart Citations